METODE PENGENDALIAN BEBAN OPERASIONAL DAN PENDAPATAN PERUSAHAAN DALAM UPAYA MENINGKATKAN LABA PERUSAHAAN DI SPBU VITKA POINT - Khadijah; Ita Mustika; Ferdila; Kharisma Familia (LPPM Universitas Ibnu Sina, 2023)
In the company's operational activities, it is necessary to control operational expenses and income to obtain the expected profit. The control system is a very important part of the company because, with the control system, the company will achieve the desired goals such as creating a good control environment. PT. Batamindo Pertiwi runs the business of trading fuel oil for the public at public refueling stations (SPBU), which are known to the people of Batam as SPBU Vitka Point No. 14,294,722. The method used by the Vitka Point gas station to control operational expenses is to perform Service Excellence or excellent service. This study aims to provide an understanding and know the effectiveness, as well as the impact of the method of controlling operating expenses and income created and implemented by the company. This type of research is qualitative with a descriptive explanation by describing the method of controlling operating expenses and the company's income. The data processed is the 2018-2020 profit and loss report data belonging to the Vitka Point gas station, with data collection techniques using interviews and direct observation. The results of the discussion from this study are that operational expense control is very effective where the emphasis on costs on operational activities has succeeded in reducing operational costs incurred as well as effective income control in stabilizing income in the ongoing Covid pandemic.